1973
DOI: 10.4039/ent105485-3
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF FUNGI AND MOISTURE ON THE LOCOMOTORY BEHAVIOR OF THE RUSTY GRAIN BEETLE, CRYPTOLESTES FERRUGINEUS (COLEOPTERA: CUCUJIDAE)

Abstract: Adults of the rusty grain beetle, Cryptolestes ferrugineus (Stephens), were placed on the surface of grain in plastic cylinders. After 48 hours records were taken of the number passing through a perforated brass screen at the bottom of the cylinders and into petri dishes containing wheat inoculated with different species of fungi. More adults were found in dishes of spoiled grain containing a mixture of fungi than in empty (control) dishes or dishes with water. The largest number were found in dishes containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The Oryzaephilus mixed sex cultures from which frass was collected, typically contained visible fungal growth which may have been used as an additional food source (Sinha 1968). Furthermore, insects (Dolinski and Loschiavo 1973) and mites (Vanhaelen et al 1979) are attracted to fungal volatiles in laboratory bioassays. Metabolites of fungi or yeasts associated with the insect gut may serve as components of an attractive pheromone, as has been found for the Scolytidae (Brand et al 1976;Brand et al 1977).…”
Section: Resultsmentioning
confidence: 99%
“…The Oryzaephilus mixed sex cultures from which frass was collected, typically contained visible fungal growth which may have been used as an additional food source (Sinha 1968). Furthermore, insects (Dolinski and Loschiavo 1973) and mites (Vanhaelen et al 1979) are attracted to fungal volatiles in laboratory bioassays. Metabolites of fungi or yeasts associated with the insect gut may serve as components of an attractive pheromone, as has been found for the Scolytidae (Brand et al 1976;Brand et al 1977).…”
Section: Resultsmentioning
confidence: 99%
“…Surtees (1965) found that the RGB adults accumulated as much in pockets of damp grain as in damp grain infested with mold. Compared with olfactory stimuli, response to humidity (when grain was damp) is a minor factor influencing adult movement, because hygrotactic stimuli inside damp grain do not increase the number of adults moving down (Dolinski and Loschiavo 1973). In stored grain bins, damp grain will likely have a mold infection.…”
Section: Chemical Compound Detecting and Respondingmentioning
confidence: 99%
“…Toxicity or pathogenicity can be affected by many factors such as temperature, moisture, and kind of substrate. At different grain storage conditions, therefore, responses by RGB adults to fungus-infected grain is different, because this response is influenced by grain moisture content, temperature, fungal species, potency and concentration of the stimulative component, stage of development of the fungus, and the presence of deterrents (Dolinski and Loschiavo 1973).…”
Section: Chemical Compound Detecting and Respondingmentioning
confidence: 99%
See 1 more Smart Citation
“…[16]. This behavior may be synergized with the response to volatile chemicals and moisture content because insect also tend to move to damp grain [51].…”
Section: Interaction Of Insect and Fungimentioning
confidence: 99%